2008
DOI: 10.1016/j.jaci.2007.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Reducing asthma health disparities in poor Puerto Rican children: The effectiveness of a culturally tailored family intervention

Abstract: Background-Island and mainland Puerto Rican children have the highest rates of asthma and asthma morbidity of any ethnic group in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 28 publications
4
108
0
Order By: Relevance
“…For example, a study of 267 African American caregivers who received a 5-series asthma self-management education program administered by parent facilitators in local community sites resulted in improved knowledge, quality of life, and perceived asthma control for the caregiver. 67 Similarly, Canino et al 68 found that asthma education intervention that included 8 modules for Puerto Rican families administered by asthma counselors resulted in significantly more symptom-free nights, improved quality of life, and self-efficacy scores in intervention groups as reported by caregivers. Unfortunately, community-based education is not widely available, and most black caregivers do not have access to information that is culturally appropriate or sensitive.…”
Section: Social/educational Interventionsmentioning
confidence: 98%
“…For example, a study of 267 African American caregivers who received a 5-series asthma self-management education program administered by parent facilitators in local community sites resulted in improved knowledge, quality of life, and perceived asthma control for the caregiver. 67 Similarly, Canino et al 68 found that asthma education intervention that included 8 modules for Puerto Rican families administered by asthma counselors resulted in significantly more symptom-free nights, improved quality of life, and self-efficacy scores in intervention groups as reported by caregivers. Unfortunately, community-based education is not widely available, and most black caregivers do not have access to information that is culturally appropriate or sensitive.…”
Section: Social/educational Interventionsmentioning
confidence: 98%
“…11 Psychological empowerment is believed to facilitate the appropriation of medical knowledge and reinforce psychosocial skills, thus increasing self-efficacy with regard to disease and treatmentrelated behaviors. 12,13 Recent work has found family-level interventions rooted in theories of psychological empowerment to be effective in improving pediatric asthma management 14,15 and improving metabolic function in children with diabetes. 16 As such, targeted interventions in psychological empowerment might hold promise for improving FAQOL in families living with food allergy.…”
Section: Introductionmentioning
confidence: 99%
“…organ transplantation. [12][13][14][15] However, these inequalities in the prevalence and treatment of OM in children in the United States have not been thoroughly explored. The objective of this study was to systematically review published studies that report on racial/ethnic or socioeconomic disparities involving the diagnosis or treatment of otitis media within the United States.…”
Section: Introductionmentioning
confidence: 99%